Prehistoric hunting megastructures in the Adriatic hinterland - Dimitrij Mlekuž Vrhovnik; Tomaž Fabec (Proceedings of the National Academy of Sciences, 2025)
Airborne laser scanning survey of the Karst Plateau in the Adriatic hinterland has revealed four monumental dry-stone structures, characterized by long, low stone alignments converging into concealed enclosures. These features, strategically placed along natural movement corridors, appear to have been designed to guide and trap herds of wild animals. Their architectural scale, complexity, and integration with the terrain suggest a high degree of communal organization, landscape knowledge, and planning. Although direct dating remains inconclusive, associated stratigraphy indicates they were abandoned before the Late Bronze Age, pointing to a potentially earlier origin. These structures may represent the westernmost examples of a broader tradition of large-scale hunting installations previously known only from the arid zones of Southwest Asia and North Africa. Their finding challenges prevailing models of prehistoric subsistence in Europe and opens broad perspectives on social organization, mobility, and human–animal relations in complex landscapes.